A Unique Presentation of Bacterial Group G Streptococcus Myopericarditis - Sacide S. Ozgur MD; Nida Ansari DO; Alan Alcantara MD; Angela Pais Vidreiro BS; Ryan Rahman; Yezin Shamoon MD; Sherif Elkattawy DO; Rachel Abboud DO; Rajkumar Doshi MD; Fayez Shamoon MD (SAGE Publishing, 2024)
Perimyocarditis and myopericarditis are inflammatory conditions of the pericardium and myocardium, often of idiopathic or infectious etiology, with viral infections being the most common. Nonrheumatic streptococcal myopericarditis (NSM) is a rare condition that can mimic acute myocardial infarction. This case report presents a 22-year-old male with no prior medical history who developed NSM following a streptococcal pharyngitis infection. The patient presented with pleuritic chest pain, tightness, and decreased exercise tolerance. Laboratory studies revealed elevated troponin levels and positive Streptococcus G antigen. Treatment included ampicillin-sulbactam, colchicine, ibuprofen, and dexamethasone. The patient's symptoms resolved, and he was discharged with amoxicillin-clavulanate, colchicine, and ibuprofen.